PENGARUH MEDIA PERENDAMAN NaCl TERHADAP LAJU KOROSI PADA BAJA ST 42 DALAM EKSTRAK INHIBITOR KULIT PISANG KEPOK - Ramza, Ramza; Magga, Ramang; Pirade, Yulius S. (Foristek, 2022)
Effect of NaCl Immersion Media on Corrosion Rate on ST 42 Steel in Kepok Banana Peel Inhibitor Extraction. This study aims to determine the corrosion rate of ST 42 steel using an inhibitor of kepok banana peel extraction with various NaCl immersion media. Sample immersion time is 168, 336, 504 hours. The method used to calculate the corrosion rate is to measure the weight loss. The sample of this research was carried out in the Mechanical Engineering laboratory, Faculty of Engineering and the Pharmacy laboratory, Faculty of Mathematics and Natural Sciences, Tadulako University. The results obtained in the variation of NaCl 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, inhibitor kepok banana peel extraction 300 ppm, an increase in corrosion rate with increasing NaCl variation with the same amount of extraction inhibitor, this is because the percentage of NaCl variation greatly affects the corrosion rate.